Structural Behaviour of Pre-Cast Concrete Sandwich Panel under Axial and Lateral Loading - Abbaker, Abdelfattah Elnur (1999)
The sandwich panel is a layered structural system composed of a low density core material bonded to and acting integrally with, a relatively thin high strength facing materials held together by shear connectors which gives different degree of composite action. In a load bearing wall the two facings act as slender columns continuously supported by shear connectors. Core material usually act as insulation material to reduce the temperature inside the building. The bending action due to eccentric load or lateral load is resisted by the tensile and compressive forces developed in outer layers while shear forces are resisted by the shear connectors. Sandwich panels are used as exterior walls in multi-unit, residential, commercial and ware house building, providing structurally and thermal efficient building element. In this study, the structural behaviour of reinforced concrete sandwich wall panels has been investigated experimentally in pre and post-cracking phase. Each panel consists of two outer reinforced concrete layers, interconnected together by different layout reinforced concrete ribs, which act as shear connectors. Three layouts of shear connectors have been selected for the study; these are continuous vertical concrete ribs and truss type layout ribs inclined at 45° and 67.5° with the vertical. Finite element method has been used in analysis for comparison with the experimental test results in the pre-cracking phase and to determine the stress distribution developed in the different components of the sandwich panel under different loading conditions. Six specimens of reinforced concrete sandwich panels (two identical specimens for each shear connector layout) each of size 1 200 x 2400 mm (width x height) have been cast in the laboratory and tested in vertical position under incremental vertical axial, lateral, and combined axial and lateral loading. The effect of different shear connector layout on the overall structural behaviour of the panel is highlighted. Moreover the composite behaviuor of the sandwich panels, the percentage of load transferred to the ribs and the crack pattern have been investigated and discussed. The structural response of the sandwich panel in term of deflections have been found equal to 35 mm, 27 mm and 22 mm for panels type A, B and C respectively. The lateral collapse load of the tested panels, have been found equal to 97 KN, 40 KN and 45 KN for panels type A, B and C respectively. From the results obtained in this study, it has been found that the sandwich panel with vertical shear connector has a better overall structural response as reflected in the integrity of the sandwich wall panel systems under the action of combined axial and lateral loads, in comparison to sandwich panels with inclined layout shear connectors.